Teaching organization and work teams formation - Ruíz Torres, Francisca (2019)
The research work addresses the problem of teacher disorganization and the lack of work teams in educational institution No. 821205 of Bellavista Baja de Combayo, district of La Encañada, province and department of Cajamarca. The problematic situation is presented and then with the application of problem analysis techniques the central problem of this educational institution is determined. Then there is a review of the theory and approaches that support the work on the organization from the business and educational point of view. The theory of human relations, the subsequent contributions on human resources and systems thinking are the basis of the theoretical model. The organization becomes a key issue in the knowledge society, so much so that some authors conceive a society composed of organizations. There is also the analysis and discussion of the results of the instruments used, the proposal with its respective foundation and the strategies to develop it. The organization in teams is the model of the proposal. An organization composed of four work teams is proposed: management, pedagogical, research and cultural contribution and evaluation. Each team has its specific objectives and responsibilities according to the vision of the organization.